The Role of Academic Supervision in Strengthening Professional Identity Among Early-Career Teachers - Bakri Bakri (Asian Journal of Applied Education (AJAE), 2026)
Strengthening professional identity among novice teachers is a critical issue, as early career stages often involve gaps between theoretical preparation and classroom practice. This qualitative case study examines the role of academic supervision in reinforcing the professional identity of senior high school teachers in South Tangerang City. Data were collected from 12 informants—six novice teachers, three principals, and three academic supervisors—through in-depth interviews, classroom observations, and document analysis, and analyzed using thematic coding. The findings indicate that academic supervision positively supports professional identity formation through constructive feedback, personalized mentoring, facilitated post-observation reflection, and assistance in developing curriculum-aligned teaching tools. The study concludes that the effectiveness of supervision depends on supervisor competence and a supportive school culture, contributing to the development of collaborative supervision models that promote continuous professional growth among novice teachers.